Ulam Asu: Advocacy Against the Dog Meat Trade in Bali - yogi antari (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
Ulam Asu is a documentary movie about dog meat trade in Bali directed by I Putu Raditya Pandet. Released in 2018, Ulam Asu has been used to advocate the resistance against the dog meat trade by Yayasan Seva Bhuana through their education program. Yayasan Seva Bhuana is a local foundation that works in improving animal welfare in Bali and concern in dog meat trade issues. Historically and culturally, the Bali dogs have a close relationship with Balinese life. Balinese people and the Bali dogs live side by side. The Bali dogs even have a special position in Balinese ceremony called caru. This research will discuss how Ulam Asu is used as video advocacy by Yayasan Seva Bhuana and how Ulam Asu works as media resistance against the dog meat trade. This research was carried out with descriptive qualitative methods. Through the elements of the movie, Ulam Asu presents a strong emotional influence. It is able to connect the audience with personal stories that they have experienced with Bali dogs. Yayasan Seva Bhuana uses Ulam Asu in their educational program as a process of integrating documentary movie into advocacy efforts. Real results and impact on the campaign against the dog meat trade were achieved by building public awareness through the video advocacy. Keywords: Bali dog, dog meat, advocacy, documentary, resistance